Tau aggregates improve the Purinergic receptor P2Y12-associated podosome rearrangements in microglial cells - Chinnathambi, Subashchandrabose; Das, Rashmi; Desale, Smita Eknath (Biochimica Et Biophysica Acta-Molecular Cell Research, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that is associated with protein misfolding, plaque accumulation, neuronal dysfunction, synaptic loss, and cognitive decline. The pathological cascade of AD includes the intracellular Tau hyperphosphorylation and its subsequent aggregation, extracellular Amyloid-& beta; plaque formation and microglia-mediated neuroinflammation. The extracellular release of aggregated Tau is sensed by surveilling microglia through the involvement of various cell surface receptors. Among all, purinergic P2Y12R signaling is involved in microglial chemotaxis towards the damaged neurons. Microglial migration is highly linked with membrane-associated actin remodeling leading to the phagocytosis of extracellular Tau species. Here, we studied the formation of various actin structures such as podosome, lamellipodia and filopodia, in response to extracellular Tau monomers and aggregates. Microglial podosomes are colocalized with actin nucleator protein WASP, Arp2 and TKS5 adaptor protein during Tau-mediated migration. Moreover, the P2Y12 receptors were associated with F-actin-rich podosome structures, which signify the potential of Tau aggregates in microglial chemotaxis through the involvement of actin remodeling.
Keywords: Alzheimer `s disease; Filopodia; microglia; Podosome; Tau aggregates